Relevance of Local Wisdom to Tourism Education for Fisheries Resources Conservation (The Case Study in West Java Province, Indonesia) - Atikah Nurhayati; Dian Yuni Pratiwi; Pringgo Kusuma Dewi Noor Yadi Putra; Isni Nurruhwati; Indah Riyanti; Titi Herawati (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2021)
Local wisdom that exists in the community is a culture of social institutions that occurs through an educational process, as in West Java Province. The potential for the development of tourism education for fisheries resource conservation through local wisdom approaches continues to be carried out by local governments. This research aims to analyze the relevance of local wisdom to fisheries resource conservation tourism education. The research method used is quantitative description and used primary and secondary data. Research time was carried out February - June 2020 and using purposive sampling 30 respondents using a questionnaire. The analytical tool used validity, reliability, and Spearman's rank correlation coefficient. Based on the research results, West Java Province has a conservation management area based on local wisdom, in Kuningan and Tasikmalaya Regency. Local wisdom that is formed the community through an educational process carried out by collaborating natural tourism with social, economic and environmental aspects. The factors form local wisdom of tourism education fishery resource conservation, that is internal variables of society, which includes beliefs, attitudes and myths as well as external variables that include binding customary norms and policies of local governments to protect and manage conservation of fisheries resources.